Efficacy and Safety of IDegAsp in a Real-World Korean Population with Type 2 Diabetes Mellitus - Shinae Kang; Yu-Bae Ahn; Tae Keun Oh; Won-Young Lee; Sung Wan Chun; Boram Bae; Amine Dahaoui; Jin Sook Jeong; Sungeun Jung; Hak Chul Jang (Diabetes & Metabolism Journal)
Background This study investigated the real-world efficacy and safety of insulin degludec/insulin aspart (IDegAsp) in Korean adults with type 2 diabetes mellitus (T2DM), whose insulin treatment was switched to IDegAsp. Methods This was a multicenter, retrospective, observational study comprising two 26-week treatment periods, before and after switching to IDegAsp, respectively. Korean adults with uncontrolled T2DM treated with basal or premix insulin (±oral antidiabetic drugs) were enrolled. The primary objective was to compare the degree of glycosylated hemoglobin (HbA1c) change in each 26-week observation period. The analyses included changes in HbA1c, fasting plasma glucose (FPG), body weight, proportion of participants achieving HbA1c <7.0%, hypoglycemic events, and total daily insulin dose (ClinicalTrials.gov, number NCT04656106). Results In total, 196 adults (mean age, 65.95 years; mean T2DM duration, 18.99 years) were analyzed. The change in both HbA1c and FPG were significantly different between the pre-switching and the post-switching period (0.28% vs. –0.51%, P<0.001; 5.21 mg/dL vs. –23.10 mg/dL, P=0.005), respectively. After switching, the rate of achieving HbA1c <7.0% was significantly improved (5.10% at baseline vs. 11.22% with IDegAsp, P=0.012). No significant differences (before vs. after switching) were observed in body weight change, and total daily insulin dose. The rates of overall and severe hypoglycemia were similar in the two periods. Conclusion In real-world clinical practice in Korea, the change of insulin regimen to IDegAsp was associated with an improvement in glycemic control without increase of hypoglycemia, supporting the use of IDegAsp for patients with T2DM uncontrolled with basal or premix insulin.